2015
DOI: 10.1111/apm.12356
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood monocyte and T‐lymphocyte activation levels at diagnosis predict long‐term survival in head and neck squamous cell carcinoma patients

Abstract: This study was performed to determine whether peripheral blood (PB) monocyte and/or lymphocyte activation at diagnosis were associated with long-term prognosis in patients with head and neck squamous cell carcinoma (HNSCC), and to what extent such prognostic properties relate to human papilloma virus (HPV)-associated tumor infection of the included patients. This was a long-term prospective study describing patient survival in relation to PB T lymphocyte and monocyte activation in patients observed for up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
5
13
1
Order By: Relevance
“…the MNP system, and the adaptive immune system are independently affected by the cancer disease. We have previously shown the same to be the case with stimulated monocyte MCP-1 secretion combined with T lymphocyte CD69 expression [13]. For this reason, several individual lines of measurement show similar results.…”
Section: Discussionsupporting
confidence: 67%
“…the MNP system, and the adaptive immune system are independently affected by the cancer disease. We have previously shown the same to be the case with stimulated monocyte MCP-1 secretion combined with T lymphocyte CD69 expression [13]. For this reason, several individual lines of measurement show similar results.…”
Section: Discussionsupporting
confidence: 67%
“…In particular, patients with evidence of a high functioning in both the adaptive and natural immune systems had a serious prognosis. Similar results were obtained with monocyte chemo‐attractant protein (MCP)‐1 secretion and the percentage of CD69‐positive lymphocyte analyses . As stimulated by LPS, HNSCC monocyte function is therefore known to predict prognosis, and in the current study we aim to investigate monocyte function upon cancer‐associated stimuli.…”
Section: Introductionsupporting
confidence: 69%
“…Several authors have shown that the functional status of the immune system is related to the prognosis of HNSCC . Furthermore, the immune system participates in the eradication of HPV‐positive (+) tumour cells during radiotherapy and also presumably so among HPV‐negative (−) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Oppositely, while CIBERSORT did not find a differential infiltrate related to the monocyte infiltrate in the M vs. NM cohorts, MIXTURE found that the monocyte population was significantly increased in the metastatic (M) group ( Figure 4B). This finding is supported by a previous study in HNSCC showing that patients with high monocyte frequency had lower survival with 8% 5-year overall survival (OS) compared to 65% 5-year OS for patients with low activation levels (Aarstad et al 2015). Although this study was performed on peripheral blood, it shows a link between increased monocyte activation and decreased survival in HNSCC patients.…”
Section: Pfs and Ossupporting
confidence: 83%